2004
DOI: 10.1530/rep.1.00272
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and proliferative responses in human and ovine ovarian surface epithelial cells

Abstract: The majority of ovarian cancers (> 90%) are believed to derive from the ovarian surface epithelium (OSE); a single layer covering the entire surface of the ovary. At ovulation, the OSE cell layer undergoes an inflammatory response, involving cell death and growth, in order to overcome ovarian surface rupture. Abnormalities during these processes are believed to contribute to the development of tumours. Using primary cultures of OSE cells, we have compared anti-inflammatory and proliferative responses directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The following collection of published studies illustrates this point effectively. FSH possibly increases proliferation in the OSE and cancer cells (90, 134,136,141,143,[161][162][163][164][165], yet in other studies, no association (166) and even reduced proliferation have been observed (167,168). Some studies have reported the stimulatory effect of LH/hCG on cell growth (90, 136, 161, 163-165, 169 -173).…”
Section: B Proliferationmentioning
confidence: 99%
“…The following collection of published studies illustrates this point effectively. FSH possibly increases proliferation in the OSE and cancer cells (90, 134,136,141,143,[161][162][163][164][165], yet in other studies, no association (166) and even reduced proliferation have been observed (167,168). Some studies have reported the stimulatory effect of LH/hCG on cell growth (90, 136, 161, 163-165, 169 -173).…”
Section: B Proliferationmentioning
confidence: 99%
“…Recombinant human CTGF (rhCTGF) was produced essentially as described previously (25) Briefly, rh CTGF was produced in a baculovirus expression system using Hi5 cells adapted for suspension growth and virus containing a complete human CTGF cDNA. Cells were cultured in Sf 900 II SFM (Life Technologies) supplemented with 20 g/ml gentamicin (CellGro) and 1X lipid (Life Technologies) and then scaled up for production in 3L Fernbach culture flasks (Corning, Corning, NY).…”
Section: Preparation and Analysis Of Recombinant Human Ctgfmentioning
confidence: 99%
“…Human ovarian surface epithelium cell cultures have been set up mostly in order to study the anti-inflammatory and proliferative responses of ovarian surface epithelium cells [4, 5] and to elucidate the mechanisms of ovarian cancer formation [69]. During the last few years, there have also been more reports on the human ovarian surface epithelium stemness, that is, on the epithelial-mesenchymal transitions [1012].…”
Section: Introductionmentioning
confidence: 99%